2016
DOI: 10.1080/23802359.2016.1155426
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome sequence of Artemisia fukudo Makino (Asteraceae)

Abstract: In this study, a complete chloroplast genome sequence of Artemisia fukudo (Asteraceae family) was characterized by de novo assembly using whole genome sequence data. The chloroplast genome was 151,011 bp in length, comprising a large single-copy region of 82,751 bp, a small single copy region of 18,348 bp and a pair of inverted repeats of 24,956 bp. The genome contained 80 protein-coding genes, 4 rRNA genes and 30 tRNA genes. Phylogenetic tree revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
1
11
0
2
Order By: Relevance
“…Among them, LSC and the 72 shared-protein-sequences tree showed the most similar topological structures and were consistent with the phylogeny of 21 Korean Artemisia species reconstructed by trnL _ trnF markers [27]. However, although some Artemisia cp data have been published, other studies contained only one to four Artemisia species [2226], and it is difficult to obtain more phylogenetic data to support our results.…”
Section: Discussionsupporting
confidence: 84%
“…Among them, LSC and the 72 shared-protein-sequences tree showed the most similar topological structures and were consistent with the phylogeny of 21 Korean Artemisia species reconstructed by trnL _ trnF markers [27]. However, although some Artemisia cp data have been published, other studies contained only one to four Artemisia species [2226], and it is difficult to obtain more phylogenetic data to support our results.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have reported that A. gmelinii and A. capillaris contain useful metabolites with various pharmacological effects such as anti-infective and anti-oxidant activity and hepatoprotective and antifibrotic effects (K€ oncz€ ol et al 2012;Wang et al 2012). However, to date, genetic and genome research related to barcoding system lack in Artemisia genus, despite the importance of herbal medicine authentication system is increased (Liu et al 2013;Lee et al 2016). In this study, we Figure 1.…”
Section: Main Textmentioning
confidence: 74%
“…The highquality paired end sequences of 2.1 and 1.6 Gb were generated from A. gmelinii and A. capillaris, respectively, and separately assembled using CLC genome assembler (v. beta 4.6, CLC Inc., Lyngby, Denmark). Afterwards, contigs representing chloroplast sequence were retrieved, ordered and combined into a single draft sequence by comparing chloroplast genomes of A. frigida (JX293720, Liu et al 2013) and A. fukudo (KU360270, Lee et al 2016). The complete genome of A. gmelinii and A. capillaris were deposited in GenBank (A. gmelinii: KU736962 and A. capillaris: KU736963).…”
Section: Main Textmentioning
confidence: 99%
“…It also has various biological effects, including anti-inflammatory, antitumor, and antibacterial properties. 40 Artemisia gmelinii Weber ex Stechm. is a plant of the high-altitude regions of Asia.…”
mentioning
confidence: 99%